Northwest view of the fair on the River Thames during the Great Frost 1683-84 - Stow, James (Tufts Archival Research Center, 2008)
From an original painting by Wyke in the British Museum. Taken from the Temple Stairs, looking towards London Bridge. This illustration is from Robert Wilkinson's "Londina Illustrata," vol. 1.